Rancang Bangun Robot Pelontar dan Penghadang Bola Sebagai Mesin Latih Permainan Bola Basket Berbasis Kendali Wireless - Akhmad Rizal Dzikrillah; Dewa; Ahmad Faiz Rahmatullah; M. Ikhwan Tantowi; Fadhillah Al Ghifari; Muhammad Fadilah Rafli; Muhammad Fawwaz Majid Alamy (Prosiding Seminar Nasional Teknoka, 2025)
Basketball players need to train their ability to pass and catch the ball from teammates amid the defense of opposing players. With the use of robotic technology, which is now commonly applied in sports training and considered more stable and controllable than humans, athletes can further improve their performance. This study aims to design and develop a ball launching machine that can be used for passing the ball and has an additional capability to block incoming shots. The system uses a net as a blocker that can be raised and lowered to intercept the launched ball. High-torque and high-speed motors on the launching wheels allow the ball to be thrown up to a distance of 4.5 meters. By using a combination of four omniwheels, the machine is capable of moving with three degrees of freedom: forward–backward, turning right–left, and sliding right–left.